Experimental investigation of modular buckling-restrained energy dissipaters with detachable features. (September 2020) - Wang, Chun-Lin; Zhao, Jing; Gao, Yuan; Meng, Shaoping
ABSTRACT: In this study, a new modular energy dissipater (MED) consisting of an inner assembled core and outer restraining tube was developed. The inner core is fabricated by multiple identical energy dissipation units with threaded couplers in series. The outer tube is used to restrain the overall buckling of the inner assembled core. The MED is characterized by a standardized design, uniform process, modular assembly and units that are easy to replace after an earthquake. Seven energy dissipaters were tested to compare the hysteretic performance and failure mode of the MED with those of a nonmodular energy dissipater (NMED) under a low-cycle loading pattern. Test results showed that the hysteretic curves of the MED were plump in shape without pinching and did not exhibit a significant reduction in strength, and the axial deformation of MEDs is up to 4% before failure. The MED specimens perform an excellent low-cycle fatigue life. The mechanical connection in the assembled core of the MED resulted in significant slip deformation that could improve the low-cycle fatigue life of the MED compared with that of the NMED at the same strain amplitude. By adding the screws in the position of the threaded connection to form a thread-screw connection, the slip deformation could be considerably diminished. Compared with the NMED specimens, the initial axial stiffness of the MED specimens was lower; therefore, a computational formula for the initial elastic stiffness was proposed. All components, including the energy dissipation units, threaded couplers and end connection units, can be detached freely during the experiments, where the threaded couplers and connection units can be reused many times. The performance of the MED shows a minimum relationship with the reused energy dissipation units. Highlights: A new modular energy dissipater (MED) is proposed. Test results show that MED exhibit good low-cycle fatigue performance. Mechanical connections in the assembled core of MED result in slip deformation. Theoretical initial stiffness formula with correction factor of 0.75 is suggested. The computational formula is obtained to estimate the slip deformation value.